Laramide transpression and oblique thrusting in the northeastern Front Range, Colorado: 3D kinematics of the Livermore Embayment - Larson, Scott M., author; Erslev, Eric A., advisor; Magloughlin, Jerry F., committee member; Charlie, Wayne A., committee member (Colorado State University. Libraries, 2009)
Basement-involved foreland orogens commonly contain anastomosing networks of bifurcating basement arches flanked by arch-bounding thrusts which commonly alternate flanks and vergence directions along strike. Transition zones, where thrust vergence reverses along the strike of an arch, exhibit three-dimensional structural complexities due to diverse trends and geometries of secondary faults and folds. The role of diversely-oriented, secondary structures in accommodating three-dimensional strain across transition zones is the fundamental problem driving this investigation. This investigation analyzed the kinematics and three-dimensional geometry of the Livermore Embayment, a transition zone which accommodated the reversal in the tectonic vergence of thrusts bounding the northeastern Front Range and southeastern Laramie Range. The Livermore Embayment is a rhomb-shaped embayment of the lower Fountain Fm. bounded by the North Livermore, West Livermore and Livermore faults and the N- and NE-trending Grayback, Roberts, and Horseshoe monoclines. Minor fault data (n=3326) from 72 locations and joint attitudes (n=1087) from 19 locations were collected from the Proterozoic basement and upper Paleozoic and Mesozoic sedimentary strata. Kinematic data, bedding attitude data (n=1048), time- and depth-structure contour maps from proprietary seismic data, and depths of formation tops from >100 wells were used to constrain 18 balanced cross sections and a 3D structural model. Compton ideal σ1 analysis of minor fault data shows regional Laramide σ1 was subhorizontal and unidirectional at 085°, refuting previous hypotheses for the area invoking a dominance of vertical motions during Laramide deformation. Variable σ1 trends at individual locations provide evidence for strain partitioning and vertical axis rotation within E-, and NE-trending transpressional structures. Relative-timing relationships of faults to joints and a 058° trend of master joints suggest a late-Laramide timing of extensional fracturing. An average trend of 149° for cross joints are consistent with a mid- to late-Miocene timing of normal faulting in the western Front Range. The proximity of the Livermore Embayment to the Proterozoic Skin Gulch Shear Zone (SGSZ) and the abrupt changes in trend and geometry of secondary structures to parallel the ENE-trend of the SGSZ are suggestive of regional fault reactivation. Kinematic data, paleomagnetic data, 2D structural modeling, and 3D block balancing all suggests the Livermore Embayment is a transpressional, right-lateral shear zone accommodating a transition between oppositely-vergent, conjugate Laramide thrusts. The Livermore Embayment itself is the product of localized transpression and highly-oblique thrusting on subvertical pre-existing faults, with the lateral translation of fault blocks limiting crustal thickening on neo-formed Laramide thrusts.
Department Head: Sally J. Sutton.